The extremely populated globular cluster system of the lenticular galaxy NGC 6861 - Escudero, Carlos Gabriel (2015)
We present a photometric study of the globular cluster (GC) system associated with the lenticular galaxy (S0) NGC 6861, which is located in a relatively low density environment. It is based on Gemini/GMOS images in the filters g′, r′, i′ of three fields, obtained under good seeing conditions. Analysing the colour-magnitude and colour-colour diagrams, we find a large number of GC candidates, which extend out to 100 kpc, and we estimate a total population of 3000 ± 300 GCs. Besides the well-known blue and red subpopulations, the colour distribution shows signs of the possible existence of a third subpopulation with intermediate colours. This could be interpreted as evidence of a past interaction or fusion event. Other signs of interactions presented by the galaxy are the non-concentric isophotes and the asymmetric spatial distribution of GC candidates with colours (g′ - i′)0 > 1.16. As observed in other galaxies, the red GCs show a steeper radial distribution than the blue GCs. In addition, the spatial distribution of these candidates exhibits strong signs of elongation. This feature is also detected in the intermediate subpopulation. On the other hand, the blue candidates show an excellent agreement with the X-ray surface brightness profile, outside 10 kpc. They also show a colour-luminosity relation (blue tilt), similar to that observed in other galaxies. A new distance modulus has been estimated through the blue subpopulation, which is in good agreement with the previous value obtained through the surface brightness fluctuation method. The specific frequency of NGC 6861 (SN = 10.6 ± 2.1) is probably one of the highest values obtained for an S0 galaxy so far.